Serum IL-18 Is a Potential Biomarker for Predicting Severe Dengue Disease Progression - Josephine Diony Nanda; Chiau-Jing Jung; Rahmat Dani Satria; Ming-Kai Jhan; Ting-Jing Shen; Po-Chun Tseng; Yung-Ting Wang; Tzong-Shiann Ho; Chiou-Feng Lin (Journal of Immunology Research)
Background. Dengue virus (DENV) infection is the most common arboviral disease that affects tropical and subtropical regions. Based on the clinical hallmarks, the different severities of patients range from mild dengue fever (MDF) to severe dengue diseases (SDDs) and include dengue hemorrhagic fever or dengue shock syndrome. These are commonly associated with cytokine release syndrome (CRS). The types and levels of cytokines/chemokines, which are suppressed or enhanced, are varied, indicating CRS’s pathogenic and host defensive effects. Principal Finding. In this study, we created an integrated and precise multiplex panel of cytokine/chemokine assays based on our literature analysis to monitor dengue CRS. A 24-plex panel of cytokines/chemokines was evaluated to measure the plasma levels of targeting factors in dengue patients with an MDF and SDD diagnosis without or with comorbidities. As identified in sixteen kinds of cytokines/chemokines, ten were significantly (P<0.05) (10/16) increased, one was significantly (P<0.01) (1/16) decreased, and five were potentially (5/16) altered in all dengue patients (n=30) in the acute phase of disease onset. Compared to MDF, the levels of IL-8 (CXCL-8) and IL-18 in SDD were markedly (P<0.05) increased, accompanied by positively increased IL-6 and TNF-α and decreased IFN-γ and RANTES. With comorbidities, SDD significantly (P<0.01) portrayed elevated IL-18 accompanied by increased IL-6 and decreased IFN-α2 and IL-12. In addition, decreased platelets were significantly (P<0.05) associated with increased IL-18. Significance. These results demonstrate an efficient panel of dengue cytokine/chemokine assays used to explore the possible level of CRS during the acute phase of disease onset; also, we are the first to report the increase of IL-18 in severe dengue with comorbidity compared to severe dengue without comorbidity and mild dengue.